Pemerolehan Bahasa Kedua pada Anak Penyandang Tunagrahita Sedang di SDLB Mambaul Ulum Paiton Probolinggo - Juwaeni Juwaeni (Balai Bahasa Sumatera Utara, 2021)
Language acquisition is not a complicated thing for children who are classified as normal. In contrast to children with special needs or disabilities. The way of acquiring language that cannot take place quickly becomes a separate obstacle for parents who are blessed with children with disabilities. This will later be problematic in the phonological realm of their second language. This problem occurred to students at SDLB Mambaul Ulum Paiton Probolinggo. Therefore, this study aims to describe the acquisition of a second language in moderately mentally retarded persons at the phonological level at SDLB Mambaul Ulum Paoiton Probolinggo. The research method used is descriptive qualitative research. While the data in this study were in the form of utterances originating from moderately mentally retarded children at SDLB Mambaul Ulum Paiton Probolinggo. The results showed that in language acquisition, the problem that often arises is that mentally retarded children have difficulty mentioning some consonant fonts. Rani and Andrey can pronounce the font with a rather clear articulation. For consonants that are nasal bilabial consonants, such as [m], [p], [b], and palatal consonants [j], Rani and Andrey pronounce perfect fonts. However, apico-alveolar consonants like [t], and [d], Rani and Andrey have a little trouble pronouncing the font. Based on the location of articulation, these fonts are inhibited consonants, namely consonants that occur because the air coming out of the lungs is completely blocked.